LINGUISTIC FOUNDATIONS OF DEVELOPING CONNECTED SPEECH IN PRIMARY SCHOOL MOTHER TONGUE EDUCATION - Reyembayeva, Arzayim Parakhatovna (SCIENCE and SOCIETY, 2026)
The article scientifically and theoretically analyzes the linguistic foundations of developing students’ oral and written coherent speech in primary native language education. It also highlights language levels (lexics and syntax), vocabulary enrichment, work on simple and compound sentences, as well as text creation mechanisms.